Programmable money: next-generation blockchain-based conditional payments - Ingo Weber; Mark Staples (Digital Finance, 2022)
Conditional payments allow the transfer of money only when pre-defined rules hold. Example uses could include welfare payments, employee expenses, insurance payouts, or tied donations. Normally, conditions are checked manually in reimbursement or pre-approval/audit processes, either at accounts before funds are distributed, or using account records after distribution. Blockchain's capabilities for smart contract and digital assets can be used to implement next-generation conditional payments, on a decentralized ledger. We conducted a project with an industry partner where we conceptualized, implemented, and evaluated a novel programmable money concept using blockchain. In the system, programmed policies are not attached to accounts, but instead to money itself. Policies here specify the conditions when money may be spent, and can be automatically checked by the money as it is spent. Policies can also define auxiliary actions to be taken as part of payment transactions, including side-payments. Policies can be dynamically added to and removed from money as it flows through an economy. These policies could be budget rules for tied funds, but could also enable new forms of "values-based money" that respect ethical or other rules which relate to societal values or social norms. We report on some of our experiences and insights regarding blockchain architecture, software engineering with blockchain, and blockchain-based programmable money. We also identify opportunities and open research questions in these areas.
Keywords: E40; E52; I38; O30; 330; Blockchain; DLT; Smart money; Programmable money; Conditional payment